Covid-19 and Spanish Flu Pandemics: Insights into the Viral Vehicles of Life and the Concept of Dispersed Organisms (Indian Journal of Public Health Research & Development, 2020)
To understand diseases at a deeper level, we propose the concept of dispersed organisms as those havingtheir constituent units spatially, and may be even temporally, separated in existence but still conformingto the definition of being an organic wholeness, having functionally dependent and non-spatio-temporallyinterconnected components. A living organism is characterized by elementary units (cells), each having thesame DNA. This definition though specifically valid for multicellular complex organisms (eukaryotes), canvery well be extended to include localized bacterial colonies as is evidenced by the phenomenon of quorumsensing, even though the DNA may only be partially identical. Starting with quorum sensing in bacteria as apreliminary indication, quantum entanglement among component units deriving from the same initial causeas a possible explanation, we draw upon a specific deeper vision of the causes of the Spanish flu pandemicof 1918-20 to establish the concept of dispersed organisms. We discuss the COVID-19 pandemic as a similardispersed organism with its specific targets, severity, endemicity, span and consequences.
Keywords: COVID-19, Spanish flu, Pandemic, Quorum sensing, Multicellular organism